Prophylactic bilateral salpingectomy for the prevention of ovarian cancers: What is happening in Italy?. Issue 5 (September 2016) - Venturella, Roberta; Rocca, Morena; Lico, Daniela; Trapasso, Simona; Di Cello, Annalisa; Gizzo, Salvatore; Zullo, Fulvio; Morelli, Michele
Abstract : In 2011, the Society of Gynecologic Oncology of Canada encouraged physicians to discuss with their patients the risks and benefits of prophylactic bilateral salpingectomy (PBS) at the time of hysterectomy or tubal ligation for prevention of ovarian cancers (OCs). The aim of this study was to examine obstetrician–gynaecologists' knowledge, opinions and practice patterns relating to opportunistic salpingectomy in the general population. An anonymous electronic survey was sent to residents, academic and hospital staff in Italian OBGYN departments. The survey included questions on demographics, knowledge and attitudes in terms of the implementation of PBS in women at average population risk of OC. At least 80% of the 479 respondents reported performing PBS during hysterectomy for benign indications, chiefly with the intent of OC risk reduction but also to decrease the risk of reoperation and subsequent tubal pathologies. Among the 86 colleagues who do not routinely perform PBS, more than 50% stated that they have doubts regarding the benefits associated with the procedure. Most of the respondents declared that they were familiar with the literature on the topic and were aware of the data reporting the safety of the procedure, and only 21 (4.53%) had never heard of PBS. Over 40% of the respondents worked in hospitals in southern Italy. PBS as a prophylactic measure to reduce the incidence of OC is a well-known strategy among the Italian OBGYNs interviewed. Given the unequal distribution of respondents, however, wider educational initiatives should be undertaken, at least in Italy, to increase the implementation of salpingectomy among OBGYNs.